The Influence of Board Diversity on Environmental Disclosures and Sustainability Performance in Malaysia - Latif, Rohaida Abdul; Yahya, Nurul Huda; Taufil Mohd, Kamarun Nisham; Kamardin, Hasnah; Ariff, Arifatul Husna Mohd (International Journal of Energy Economics and Policy, 2020)
Sustainable growth and environmental issues have been one of the critical topics discussed by governments, legislators and environmentalists worldwide. These issues have vital impacts on the future sustainability performance of a company, societies, environment and other interrelated ecosystem. The objectives of the study are three-folds (i) to examine the extent of environmental disclosures (ER) among industrial listed companies, (ii) to examine the factors which motivate companies to disclose ER and (iii) to assess the impact of ER disclosures on sustainability performances in terms of returns on invested capital (ROIC) and sustainable growth (SG). Based on content analysis, this study finds that the level of ER disclosures is very low with an average ER Disclosure Score of only 26%. Hence more efforts are needed to motivate firms to disclose environmental activities. Using hierarchical tobit regression with robust standard error, this study finds that board diversity (Muslim directors), firm size, profitability and growth have significant influence on ER disclosures. Other board characteristics such as board size and board independence were not significant drivers of environmental disclosures. Firm size and growth had strong significant effect on one-year ahead and average 3-year future performances while the results of ER disclosures on future performances are insignificant. Keywords: environmental reporting, sustainability growth, board diversity, Muslim, gender, integrated reporting. JEL Classifications: G38, M14, Q56 DOI: https://doi.org/10.32479/ijeep.9508